Development and feasibility of a best-practice health literacy App for adults living with CKD: Presenter(s): Danielle Muscat, University of Sydney, Australia. (April 2023) - Zwi, Stephanie; Isautier, Jennifer Jennifer; Webster, Angela; Lambert, Kelly; Shepherd, Heather; McCaffery, Kirsten
Abstract : Background: Management of chronic kidney disease (CKD) presumes a high level of patient involvement both in decision-making and implementation of care. We developed a cross-platform smartphone application (the "SUCCESS app") to support haemodialysis patients from diverse culturally and linguistically-diverse backgrounds to actively participate in self-management, improve health literacy and engage in shared decision-making. The app used a two-pronged health literacy approach by adopting strategies to reduce the complexity of content related to diet, fluids, medicine, physical activity, and supportive care as well as features to improve the communicative and critical health literacy skills of patients. This included animated videos related to in-consultation question-asking and shared decision-making, as well as question prompt lists embedded within each content area. The aim of this study was to investigate the feasibility of implementing the SUCCESS App in in-centre haemodialysis units in New South Wales (NSW), Australia. Methods: We used a multi-site pre-post study design with mixed Methods: evaluation to assess feasibility. Participants>18 years receiving in-centre haemodialysis were invited to use the intervention for 12 weeks. Quantitative data were obtained at baseline and 12 weeks follow-up, and analysed using paired sample t-tests. Outcomes related to shared decision-making included the Decision Self-Efficacy Scale (Range: 1-100) and the Health Literacy Questionnaire ('Ability to actively engage with healthcare providers' domain; Range: 1-5). Findings: The SUCCESS app was successfully implemented across four local health districts in NSW, Australia (N=116). Efficacy testing showed significant improvements on 'Ability to actively engage with healthcare providers' domain of the HLQ (mean difference: 0.2; CI95%: 0.0-0.4; p=0.03) and decision self-efficacy (mean difference: 4.3; CI95% 0.6-7.9; p=0.02) after 12 weeks app use. Discussion: This is the first health literacy informed app developed to promote active patient participation in chronic kidney disease management and decision-making. Having established feasibility, a randomized controlled trial is now underway.